Multispectral control of pesticide concentrations in aquatic environments using bioindication on phytoplankton - Kvaternyuk, Sergey (Lviv Politechnic Publishing House, 2017)
The aim of the work is to improve the method and means of multispectral measurement of the content of unsuitable chemical plant protection products in aqueous media using bioindication on phytoplankton. The article analyzes the errors of indirect measurements and the reliability of the control of the concentration of pesticides using the developed means of environmental monitoring of integral parameters of pollution of water bodies.
Keywords: ecological monitoring; multispectral measurements; water; phytoplankton; bioindication